Greedy method for solvingthe langkawi touristroute: a case study - Hashim, Zakiah; Mat Desa, Wan Laailatul Hanim; Aziz, Hurul Ain; Mohd Zaki, Nur Mariana Zaimah (2018)
This paper presents a real case study to determine the optimal tourist route at Langkawi Island. The Langkawi Island was selected as the case study becausenormally, tourist travel to this island will drive the rented car as the primary mode of transport. Thus, the aim of this paperis to developa mathematical model to find an optimal route for tourist to travel to their interesting places around Langkawi Island.In order to solve the problem, Greedy methodwasapplied in this studyand MATLABversion 7.8 has beenused to get the solution.The result obtained shows that Nearest Greedy Insertion method givesbetter result compared to the Nearest Greedy method. The minimum value of theroute selection giveseffect to the cost of travelling. Therefore, from this study, the best route that connect from one interesting place to others place can be suggested to the tourist as a guidance. In addition, tourist can save their time and moneyto visit all interesting places in this study.